Effect of Organic Interface on Microelectronic Parameters of Heterojunction Device - Uğur, Ali (Fırat University, 2025)
In this study, the Ag/FK/n-Si heterojunction device was created using the Ag/n-Si diode and FK (Phenol Red) organic interface. With the help of current-voltage (I-V) measurements, important microelectronic parameters of reference and the heterojunction devices such as barrier height (?b), ideality factor (n), series resistance (Rs), and saturation current density (J0) were calculated using thermionic emission (TE) theory. In addition, the frequency values of the produced devices between 500 kHz and 1750 kHz were regularly increased and the built-in potential (Vbi), barrier height (?b), and donor concentration (Nd) were calculated from the microelectronic parameters obtained from the C-V measurement taken at different frequencies. As a result of the measurements, calculations, and comparisons obtained after the studies, it was reported that the Ag/FK/n-Si heterojunction produced was applicable in microelectronic device technologies.

Bu çalışmada, Ag/n-Si referans diyot ve FK (Fenol Kırmızı) organik ara yüzey kullanılarak Ag/FK/n-Si hetero eklem aygıtı oluşturuldu. Akım-gerilim (I-V) ölçümleri yardımıyla referans ve heteroeklem aygıtların engel yüksekliği (?b), idealite faktörü (n), seri direnç (Rs) ve doyma akım yoğunluğu (J0) benzeri önemli mikroelektronik parametreleri termiyonik emisyon (TE) teorisi kullanılarak hesaplandı. Ayrıca üretilen aygıtların 500 kHz ile 1750 kHz arasındaki frekans değerleri düzenli olarak artırılarak farklı frekanslarda alınan C-V ölçümünden elde edilen mikroelektronik parametrelerden built-in potansiyeli (Vbi), engel yüksekliği (?b), donör konsantrasyonu (Nd) hesaplandı. Yapılan çalışmalar sonrası elde edilen ölçümler, hesaplamalar ve kıyaslamalar sonucunda üretilmiş olan Ag/FK/n-Si hetero ekleminin mikroelektronik aygıt teknolojilerinde uygulanabilir olduğu rapor edildi.
Organik Arayüzeyin Heteroeklem Aygıtın Mikro Elektronik Parametrelerine Etkisi
Keywords: Condensed Matter Characterisation Technique Development; Yoğun Madde Karakterizasyon Tekniği Geliştirme